Present status and perspective on the future use of aflatoxin biocontrol products - Moral, J.; Garcia-Lopez, M.T.; Camiletti, B.X.; Jaime, R.; Michailides, T.J.; Bandyopadhyay, R.; Ortega Beltran, A. (MDPI, 2020)
Aflatoxin contamination of important food and feed crops occurs frequently in warm tropical and subtropical regions. The contamination is caused mainly by Aspergillus flavus and A. parasiticus. Aflatoxin contamination negatively affects health and trade sectors and causes economic losses to agricultural industries. Many pre- and post-harvest technologies can limit aflatoxin contamination but may not always reduce aflatoxin concentrations below tolerance thresholds. However, the use of atoxigenic (non-toxin producing) isolates of A. flavus to competitively displace aflatoxin producers is a practical strategy that effectively limits aflatoxin contamination in crops from field to plate. Biocontrol products formulated with atoxigenic isolates as active ingredients have been registered for use in the US, several African nations, and one such product is in final stages of registration in Italy. Many other nations are seeking to develop biocontrol products to protect their crops. In this review article we present an overview of the biocontrol technology, explain the basis to select atoxigenic isolates as active ingredients, describe how formulations are developed and tested, and describe how a biocontrol product is used commercially. Future perspectives on formulations of aflatoxin biocontrol products, along with other important topics related to the aflatoxin biocontrol technology are also discussed.